2020
DOI: 10.1155/2020/5364252
|View full text |Cite
|
Sign up to set email alerts
|

A Customized Deep Neural Network Approach to Investigate Travel Mode Choice with Interpretable Utility Information

Abstract: Discrete choice modeling of travel modes is an essential part of traffic planning and management. Thus far, this field has been dominated by multinomial logit (MNL) models with a linear utility specification. However, deep neural networks (DNNs), owing to their powerful capacity of nonlinear fitting, are now rapidly replacing these models. This is because, by using DNNs, mode choice can be assimilated with the classification problems within the machine learning community. This article proposes a newly designed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Comparing the interpretation results of ML models with an advanced parametric model, such as a mixed logit model, would also be valuable to validate the model further. Deep learning models [11,42] are reasonable alternatives for the XGB and RF and the proposed modelagnostic interpretation methods can still available for those models. Local interpretation methods such as local interpretable model-agnostic explanations (LIME) and Shapley additive explanations (SHAP) can contribute to better representation of the heterogeneity of individuals and groups [43,44], which has also been a critical subject of behavior analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing the interpretation results of ML models with an advanced parametric model, such as a mixed logit model, would also be valuable to validate the model further. Deep learning models [11,42] are reasonable alternatives for the XGB and RF and the proposed modelagnostic interpretation methods can still available for those models. Local interpretation methods such as local interpretable model-agnostic explanations (LIME) and Shapley additive explanations (SHAP) can contribute to better representation of the heterogeneity of individuals and groups [43,44], which has also been a critical subject of behavior analysis.…”
Section: Discussionmentioning
confidence: 99%
“…It can represent complex relationships between mode choices and input variables in a data-driven manner rather than making strict assumptions about the data [7]. Many previous studies have reported the use of an ML approach to model travel mode choice [1,[6][7][8][9][10][11]. ese authors have generally reported improvements in the prediction performance of ML approaches compared to MNLbased models.…”
Section: Introductionmentioning
confidence: 99%
“…ere is much literature on predicting air traveler repeated purchase behaviors [8,10,14,[18][19][20], but literature based on using a machine learning model to make these predictions is still limited [8,12,15]. is is especially true for actual traveler sales date, because surveys or experimental data have often been used to study traveler repeat purchases [10,18,22,26].…”
Section: Eoretical Contributionmentioning
confidence: 99%
“…is is especially true for actual traveler sales date, because surveys or experimental data have often been used to study traveler repeat purchases [10,18,22,26]. Besides, some studies have optimized other machine learning algorithms, such as artificial bee colony algorithm and deep neural network approach, to predict customer repurchase intention [12,15]. However, these studies only use consumer data in specific environments to test their proposed optimization algorithms and do not study whether these algorithms can be well applied to the business environment.…”
Section: Eoretical Contributionmentioning
confidence: 99%
See 1 more Smart Citation